Culture‐enriched community profiling improves resolution of the vertebrate gut microbiota. (9th July 2021) - Goldman, Samantha L.; Sanders, Jon G.; Yan, Weiwei; Denice, Anthony; Cornwall, Margaret; Ivey, Kathleen N.; Taylor, Emily N.; Gunderson, Alex R.; Sheehan, Michael J.; Mjungu, Deus; Lonsdorf, Elizabeth V.; Pusey, Anne E.; et al.
Abstract: Vertebrates harbour gut microbial communities containing hundreds of bacterial species, most of which have never been cultivated or isolated in the laboratory. The lack of cultured representatives from vertebrate gut microbiotas limits the description and experimental interrogation of these communities. Here, we show that representatives from >50% of the bacterial genera detected by culture‐independent sequencing in the gut microbiotas of fence lizards, house mice, chimpanzees, and humans were recovered in mixed cultures from frozen faecal samples plated on a panel of nine media under a single growth condition. In addition, culturing captured >100 rare bacterial genera overlooked by culture‐independent sequencing, more than doubling the total number of bacterial sequence variants detected. Our approach recovered representatives from 23 previously uncultured candidate bacterial genera, 12 of which were not detected by culture‐independent sequencing. Results identified strategies for both indiscriminate and selective culturing of the gut microbiota that were reproducible across vertebrate species. Isolation followed by whole‐genome sequencing of 161 bacterial colonies from wild chimpanzees enabled the discovery of candidate novel species closely related to the opportunistic pathogens of humans Clostridium difficile and Hungatella hathewayi . This study establishes culturing methods that improve inventories and facilitate isolation of gut microbiota constituents from a wide diversity of vertebrate species.